2008
DOI: 10.1016/j.neuron.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in Neuroplasticity and Neurological Disorders

Abstract: Mitochondrial electron transport generates the ATP that is essential for the excitability and survival of neurons, and the protein phosphorylation reactions that mediate synaptic signaling and related long-term changes in neuronal structure and function. Mitochondria are highly dynamic organelles that divide, fuse and move purposefully within axons and dendrites. An Major functions of mitochondria in neurons include the regulation of Ca2+ and redox signaling, developmental and synaptic plasticity, and the arbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
742
0
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 922 publications
(769 citation statements)
references
References 205 publications
(204 reference statements)
12
742
0
15
Order By: Relevance
“…On the contrary, mitochondrial dysfunction (such as energy failure and alteration of mitochondrial ROS production) is generally accepted as a prominent cause of axonal degeneration in multiple sclerosis, and two inhibitors of MPT pore formation have been shown to delay disease onset and increase survival of amyotrophic lateral sclerosis mice. 13,46 Because mitochondria (and presumably mtASIC1a) are distributed and functional in axons, 13 our study provides an alternative explanation that the protection against axonal degeneration observed in ASIC1a-deficient mice may be due to reduced activity in MPT. Taken together, our findings suggest that, besides plasma membrane ASIC1a, mtASIC1a may also be a promising target for drug design and clinical therapy.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…On the contrary, mitochondrial dysfunction (such as energy failure and alteration of mitochondrial ROS production) is generally accepted as a prominent cause of axonal degeneration in multiple sclerosis, and two inhibitors of MPT pore formation have been shown to delay disease onset and increase survival of amyotrophic lateral sclerosis mice. 13,46 Because mitochondria (and presumably mtASIC1a) are distributed and functional in axons, 13 our study provides an alternative explanation that the protection against axonal degeneration observed in ASIC1a-deficient mice may be due to reduced activity in MPT. Taken together, our findings suggest that, besides plasma membrane ASIC1a, mtASIC1a may also be a promising target for drug design and clinical therapy.…”
Section: Discussionmentioning
confidence: 80%
“…10,14,17 Therefore, although speculative, plasma membrane ASIC1a (death initiator) and mtASIC1a (death executor) may function at different levels to regulate ischemic cell death, which may cooperatively explain the observed strong neuroprotective effect in ASIC1a-knockout mice (Figure 6b). 10,13,15 It was reported that compared with WT mice, ASIC1a-deficient mice had both a markedly reduced motor deficit and decreased axonal degeneration in a mouse model of experimental autoimmune encephalomyelitis despite the similar levels of CNS inflammation. 39,43 Interestingly, ASIC1a was found only in the surface membrane of neuronal soma and dendrites but not that of axons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Incomplete processing of IMMP2L substrates seems to result in a hyperactive mitochondrion with an increased production of superoxide 16 and to promote the formation of a mitochondrial permeability transition pore which leads to release of pro-apoptotic proteins, and thereby activating cell death pathways. 17,18 In this study, we describe seven Danish TS patients with intragenic IMMP2L deletions, affecting one of two alternative IMMP2L transcripts (the previously described long transcript and a short alternative transcript with the two first exons residing within intron 3 of the long transcript). The deletions are significantly more frequent in the patients compared with the controls giving further evidence for IMMP2L as a TS susceptibility gene.…”
Section: Introductionmentioning
confidence: 97%